Pembukuan Sederhana Berbasis Handphone Pada Posdaya Kasih Ibu - Safitri Siswono; Indah Masri; Amelia Oktrivina; Annisa Tri Handari; Dina Rafifah; Devina Zahraeni; Salsa Nabila; Rizky Syauqy; Antonius Stevent (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2024)
Real Work Lecture is a student program as a form of community service with an cross-scientific and sectoral approach within a certain period of time. KKN which has been carried out at Posdaya Kasih Ibu with the theme Simple Mobile-Based Bookkeeping at Posdaya Kasih Ibu Pasar Minggu, South Jakarta. The purpose of the program being implemented is to increase the understanding of small traders at Posdaya Kasih Ibu so that it is easier to compile simple financial reports for the businesses they run, because with the financial bookkeeping the traders can know exactly how much money is spent. received, the amount of money spent, profit, loss, Break Even Point (BEP), and the proportion of capital needed to develop the business. Seeing the condition of small traders who lack knowledge about making simple financial reports, it is necessary to provide guidance to small traders in preparing simple financial reports for the business they run. The method used by KKN implementers is to provide socialization, observation and interviews regarding increasing understanding of making simple financial reports.